Synoptic taxonomy of cortaderia stapf (danthonioideae, poaceae) - Testoni, Daniel (2017)
Cortaderia (Poaceae; Danthonioideae) is a medium-sized genus of C3 tussock grasses, widespread in the temperate to tropic-alpine regions of South America. It is particularly important in the subalpine and alpine zones of the Andes. We revised the classification of the genus, and recognize 17 species grouped into five informal groups. We describe one new species, Cortaderia echinata H.P.Linder, from Peru. We provide a key to the groups and the species, complete nomenclature for each species including new lectotypes, and notes on the ecology, distribution and diagnostic morphological and anatomical characters.